Leveraging pediatric PROMIS item banks to assess physical functioning in children at risk for severe functional loss - Angie Mae Rodday; Robert J. Graham; Ruth Ann Weidner; Nan E. Rothrock; Darren A. Dewalt; Susan K. Parsons (SpringerOpen, 2017)
Abstract Background Pediatric neuromuscular illnesses often result in decreased health-related quality of life (HRQL), notably in physical functioning. Generic HRQL measures have been developed for use in general populations, but may not adequately assess patients with severe functional loss. To address this measurement gap, we created two custom parent-proxy physical functioning short forms for use among children at risk for low levels of functioning, using pediatric Patient Reported Outcomes Measurement Information System (PROMIS) item banks for Upper Extremity and Mobility. Methods Two custom short forms from PROMIS Upper Extremity (13 items) and Mobility (13 items) parent-proxy item banks were created and administered to parents of children (ages 5 - 22 years) enrolled in an integrated care program for management of chronic respiratory insufficiency, largely due to neuromuscular illnesses. Standardized PROMIS T-scores have a mean of 50 (SD = 10); higher scores indicate better functioning. Physicians rated clinical severity. Single proxy-rated items on mental and physical health from the Child Health Rating Inventories (CHRIs) global health scale were completed by parents. Psychometric properties, including known groups comparisons, were explored. Results Fifty-seven parents completed the parent-proxy custom PROMIS short forms. The mean Upper Extremity T-score was 21 (SD = 13); the mean Mobility T-score was 22 (SD = 11). Some participants scored at the measurement floor; two items on assistive devices did not perform well in this sample and were excluded from the Mobility T-score. Known groups comparisons showed that those with lower clinical severity had better median Upper Extremity (22 vs. 14, p < 0.001) and Mobility (28 vs. 16, p = 0.004) function than those with worse clinical severity. Both Upper Extremity and Mobility T-scores were higher in the subgroups defined by better physical and mental health, as measured by the CHRIs. Conclusions Upper Extremity and Mobility T-scores were nearly three standard deviations below the PROMIS pediatric calibration population mean. Preliminary psychometrics demonstrated the potential to more accurately measure lower physical functioning using items from PROMIS item banks. However, some participants scored at the measurement floor despite targeting items at the lower end of the scale. Further short form refinement, enrichment of the item banks, and larger-scale field testing are needed.